Are owners chalk and cheese in the context of dividend smoothing asymmetry? - Ali, Zahid; Hanming, Yang; Zhongxin, Wu; Ali, Shuaib (Frontiers in Psychology, 2022)
The study empirically analyzes the impact of ownership structure on dividend smoothing for the non-financial firms listed on the Pakistan Stock Exchange(PSX) for 2005-2015 via the lens of agency and information asymmetry theory. We have estimated dividend smoothing by two measures, speed of adjustment and relative volatility. The study empirically finds the impact of ownership structure on dividend smoothing (measured via speed of adjustment) via Tobit regression. We developed ownership index via principal component analysis (PCA). The study finds that individual and management ownership are positively associated with dividend smoothing, and the study found that institutional ownership positively affects dividend smoothing. Foreign ownership has the opposite impact on dividend smoothing in adjusting dividends from below and above, and they always prefer high dividends. Individual ownership has also exhibited a different impact in smoothing from below and above. Institutional owners avoid cuts and omissions and negatively affect SOA in case of adjusting dividends from above. Ownership concentration is negatively associated with dividend smoothing irrespective of whether the firm is smoothing from above or below. In contrast, management ownership negatively affected SOA in adjusting from above or below. Family firms in Pakistan smooth more to win minor shareholders' trust and signal that they sacrifice their private benefits to reduce the type II agency problem. Finally, the authors found negative association between dividend smoothing and corporate governance quality. The study found a substitution role of corporate governance with dividend smoothing in high-agency conflict firms.